Analysis of road user behavior influence on unsignalized intersection performance - Cruz, Hector Paris Troy O.; Sigua, Ricardo G. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
The main purpose of the research is to determine the potential influence of road user behavior and the corresponding road user interactions on the performance ofunsignalized intersections. Often, road users violate governing traffic control systems whenever these do not suit their demands. Traffic inconvenience ranging from congestions to car collisions result from the said violation. The various actions taken by both drivers and pedestrians determine the safety of streets. The different movements of motorists and non-motorists were observed to determine the interactions among them. Specific parameters which are either satisfied or ignored were assigned to each road user interaction. The number of occurrences of the said interactions were tallied and compared. The larger of these was considered as the governing influence pattern hence provided with measures such as counts, lengths, and durations. Recommendations on the improvement of the intersection design were given afterward. From the results, it can be said that road user behavior is a factor affecting the performance of unsignalized intersections.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Roads -- Interchanges and intersections